Analisis Program Perencanaan Penganggaran Responsif Gender (Studi di Dinas Pemberdayaan Perempuan, Perlindungan Anak, Pengendalian Penduduk dan Keluarga Berencana Kota Batu Jawa Timur) - Dody Setyawan; Firman Firdausi; Sugeng Rusmiwari (Publisia: Jurnal Ilmu Administrasi Publik, 2018)
This study aims to analyze the implementation of Gender Responsive Planning and Budgeting (PPRG) in Batu City. Analytical techniques use qualitative methods with a focus on general budgets, which incorporate gender assumptions and distribute budget allocations that take account of their gender impact. Data obtained through in-depth interviews with purposive sampling on staff and employees who know and engage in budgeting. Furthermore, to study strategic policy document of Batu City, that is; RPJMD documents, RKPD documents and APBD documents by 2016. The results of research on gender responsive planning and budgeting process in the Regional Government Work Units (SKPD) have not been fully implemented due to the fact that the Regional Regulation (Perda) has not yet been established as the basis of Gender Equality Gender (PUG) . There is no PUG Working Group at city and Focal Point level in SKPD. Budgeting also does not use gender analysis in the form of Gender Analysis Pathway (GAP) and Gender Budget Statement (GBS). In fact, these instruments become formal evidence of the existence of gender responsive planning and budgeting in Batu City Local Government.DOI: https://doi.org/10.26905/pjiap.v3i1.2275